Nerve Bundles and Deep Dyspareunia in Endometriosis. (July 2016) - Williams, Christina; Hoang, Lien; Yosef, Ali; Alotaibi, Fahad; Allaire, Catherine; Brotto, Lori; Fraser, Ian S.; Bedaiwy, Mohamed A.; Ng, Tony L.; Lee, Anna F.; Yong, Paul J.
The etiology of deep dyspareunia in endometriosis is unclear. Our objective was to determine whether nerve bundle density in the cul-de-sac/uterosacrals (zone II) is associated with deep dyspareunia in women with endometriosis. We conducted a blinded retrospective immunohistochemistry study (n = 58) at a tertiary referral center (2011-2013). Patients were stringently phenotyped into a study group and 2 control groups. The study group (tender endometriosis, n = 29) consisted of patients with deep dyspareunia, a tender zone II on examination, and an endometriosis lesion in zone II excised at surgery. Control group 1 (nontender endometriosis, n = 17) consisted of patients without deep dyspareunia, a nontender zone II on examination, and an endometriosis lesion in zone II excised at surgery. Control group 2 (tender nonendometriosis, n = 12) consisted of patients with deep dyspareunia, a tender zone II on examination, and a nonendometriosis lesion (eg, normal histology) in zone II excised at surgery. Protein gene product 9.5 (PGP9.5) immunohistochemistry was performed to identify nerve bundles (nerve fibers surrounded by perineurium) in the excised zone II lesion. PGP9.5 nerve bundle density (bundles/high powered field [HPF]) was then scored by a pathologist blinded to the group. We found a significant difference in PGP9.5 nerve bundle density between the 3 groups (analysis of variance, F 2, 55 = 6.39, P = .003). Mean PGP9.5 nerve bundle density was significantly higher in the study group (1.16 ± 0.56 bundles/HPF [±standard deviation]) compared to control group 1 (0.65 ± 0.36, Tukey test, P = .005) and control group 2 (0.72 ± 0.56, Tukey test, P = .044). This study provides evidence that neurogenesis in the cul-de-sac/uterosacrals may be an etiological factor for deep dyspareunia in endometriosis.